2017
DOI: 10.1002/cssc.201700449
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of CH3NH3PbI3 Using a Dynamically Dispensed Spin‐Coating Method: Improving Efficiency with a Reproducible PbI2 Blocking Layer

Abstract: It is commonly believed that excess PbI has beneficial effects for perovskite solar cells owing to the modification of charge-transport behavior at interfaces, by surface passivation and by blocking electron-hole recombination. Here, we introduce a dynamically dispensed spin-coating technique in a two-step deposition to form a perovskite layer with controllable quantities of crystalline PbI . Using this technique, the concentration of CH NH I solution is kept constant at the reaction interface, ensuring smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This result reveals that the excess of PbI 2 in the film and/or the interfacial intermediate phase layer modifies substantially the mechanism of nucleation, yielding in this case to isotropic MAPbI 3 .H 2 O particles. [ 20g,22 ] Figure 4b compares the evolution of the most intense XRD peaks corresponding to MAPbI 3 , MAPbI 3 .H 2 O, and PbI 2 as a function of aging time. Under the same exposure conditions, MAPbI 3 with 9 mol% excess of PbI 2 exhibits subtle variation in the degradation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This result reveals that the excess of PbI 2 in the film and/or the interfacial intermediate phase layer modifies substantially the mechanism of nucleation, yielding in this case to isotropic MAPbI 3 .H 2 O particles. [ 20g,22 ] Figure 4b compares the evolution of the most intense XRD peaks corresponding to MAPbI 3 , MAPbI 3 .H 2 O, and PbI 2 as a function of aging time. Under the same exposure conditions, MAPbI 3 with 9 mol% excess of PbI 2 exhibits subtle variation in the degradation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 From a more fundamental perspective, it has been demonstrated that recombination between charge carriers in the absorber and transport layers have been suppressed due to a thin interfacial layer of PbI 2 . [27][28][29] In regard to charge carriers that form in the perovskite absorber, both a reduction of non-radiative recombination, and accelerated recombination with an excess of PbI 2 has been reported. [30][31][32] These reports do not necessarily contradict one another but may rather reflect a dependence on where, and how PbI 2 has been introduced in the perovskite.…”
mentioning
confidence: 99%
“…That means the optical properties can be tuned by changing the ratio between halides in the perovskite structure. All of these properties are very useful for optoelectronic applications, such as solar cells, LEDs, photodetectors, and laser applications [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…relatively high charge mobility and conductivity, and low temperature particle fusion from 1D and 2D structures [16,35,36,38,137,236] NCs [24,[239][240][241][242]. MAPI is one of the well characterised 3D structured perovskite used for constructing highly efficient photodetector, solar cells and LEDs [15,[243][244][245][246][247]. Therefore, finding novel perovskite and related nanomaterials with useful relevant properties is a major area of research in this field and many researchers have been working to replace A and B groups in the ABX 3 perovskite structure with feasible atom such as Bi, In, Ag, Sn, and Cu [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation